A description of the energy levels and electric quadrupole transitions of the 92Nb and 92Mo nuclei using nuclear shell model - Mustafa .Jabbar; Fatima alfatlawi (Kuwait Journal of Science)
In current study ,92Nb and 92Mo isotopes have been determined for calculating  energy levels and electric quadrupole transition probabilities. These isotopes have different model spaces (1g9/2,1g7/2) for one proton and  (2d5/2, 1g7/2, 3s1/2, 2d3/2  and 1h11/2 ) for one neutron of 92Nb nucleus while (1g9/2, 1g7/2) orbits for two protons of  92Mo nucleus.Two interaction have been applied in this study which are surface delta and modified surface delta interactions. The calculations have been achieved by using appropriate effective charges for proton and neutron as well as parameter length of harmonic potential. Computed results have been compared with the experimental values. After this comparison, the energy values and the transition probabilities have shown good agreement with the experimental values, it has also  found that the values of the total angular momentum and parity are determined and confirmed for some of the experimental energies, undetermined and unconfirmed experimentally. Theoretically, new values of quadrupole electric transition probabilities have been explored which have not been known in the experimental data.